2001
DOI: 10.1111/j.1708-8240.2001.tb00258.x
|View full text |Cite
|
Sign up to set email alerts
|

The Science of Communicating the Art of Esthetic Dentistry. Part III: Precise Shade Communication

Abstract: Shade matching is inherently complex and involves understanding the science of color, determining the shade and surface characteristics of teeth, and communicating this information to the laboratory technician. The laboratory technician then has the difficult task of mimicking the selected shade and ultimately reproducing it in the final restoration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 10 publications
0
17
0
2
Order By: Relevance
“…From clinicians' perspective, the clinical experience has been found to lead to greater shade-matching success. [26][27][28] The laboratory authorizations also showed that the majority of these dental students did not include the dentin shade selection for all- 33 In their study, the experienced clinicians consistently chose the group with the lower ∆E. Without this information, the laboratory may not be able to adequately incorporate the hue of the underlying tooth structure to create an accurate shade-match outcome, thus adversely affecting both ∆E clinical and ∆E laboratory .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From clinicians' perspective, the clinical experience has been found to lead to greater shade-matching success. [26][27][28] The laboratory authorizations also showed that the majority of these dental students did not include the dentin shade selection for all- 33 In their study, the experienced clinicians consistently chose the group with the lower ∆E. Without this information, the laboratory may not be able to adequately incorporate the hue of the underlying tooth structure to create an accurate shade-match outcome, thus adversely affecting both ∆E clinical and ∆E laboratory .…”
Section: Discussionmentioning
confidence: 99%
“…By using the prescription shade, reference shade, and shade of luted definitive restoration, we calculated two ∆E* values with the spectrophotometer. [26][27][28] Objective dental shade-matching instruments such as the colorimeter, spectroradiometer, and spectrophotometer can also produce useful information. The ∆E clinical represented the clinical objective shade-matching outcome of luted definitive restoration.…”
mentioning
confidence: 99%
“…The ability to accurately record shade for a subsequent restoration is a difficult task for both dentist and technician. 38 Problems in producing the optimal shade when constructing fixed gingivally coloured ceramic restorations have been reported. 13 For conventional shade taking, the use of photography, diagrams, multiple shade recordings and electronic colour measure devices can help in achieving optimal shade, although the latter have not been developed for gingival shades.…”
Section: Technician-clinician Interfacementioning
confidence: 99%
“…Other technologies such as colorimeters and spectrophotometers have been introduced to the dental industry that can be useful in determining the appropriate composite shades necessary for a specific restoration by helping to ensure predictable shade matching. [19][20][21] A tristimulus colorimeter (X-Rite ® ShadeVision™ System, X-Rite, Inc., Grandville, MI, USA) measures the radiant energy for each primary color of red, blue, and green. 20 Spectrophotometers measure the amount of visible energy for each hue of the spectrum.…”
mentioning
confidence: 99%
“…20 Human subjectivity is eliminated by using precision optical measurement instruments that respond to light in a manner similar to that of the human eye but that also identify the shades of the tooth by measuring the tooth color in terms of its three attributes: hue, value, and chroma. 21 Specifically, the human eye reacts to light stimulus in complex ways that are interpreted by the visual cortex of the brain and influenced by a variety of factors, such as fatigue, environment, and emotions. 13 Each part of the eye serves a specific purpose.…”
mentioning
confidence: 99%